Sustainable Steps in the Snow: Exploring factors associated with active school commuting in Finland - Melin, Marianna C.; Tuominen, Jarno; Salo, Paula (Elsevier Ltd, 2025)
Physical inactivity of children and youth is a major health problem. Active commuting could increase the amount of physical activity and be a more environmentally friendly traffic mode choice compared with motorized vehicles. Parents have an integral role in determining the options a child has for commuting. We explored parental barriers and motivators associated with the active commute of their children.
This cross-sectional study used the CLIMATE NUDGE Survey data of parents with school-aged children. A set of 25 possible influencing factors included demographic factors, social aspects, and pro-environmental attitudes, and questions about the motivating role of journey characteristics and health effects. The data were analyzed with two multinomial logistic regression analyses (N = 320): first, comparing those who either never or sometimes commute actively to those who always do so, and second, those who always or sometimes commute actively to those who never do so.
Results indicated the strongest determinants to differentiate those who always and those who never use active commute, were commute distance and parental beliefs about social commute norms. The longer the commute distance was, the more likely the child was to belong to the never active commuter group and less likely to belong to the always active commuter group. The more parents believed their child's peers commuted actively, the more likely it was that their child always commuted actively and less likely they never did so.
We found several factors associated with active commuting, yet somewhat surprisingly neither environmental attitudes nor climate change related reasons were significantly associated with active commuting. To conclude, instead of highlighting environmental aspects to promote active commute, we recommend highlighting social norms and perception of the commute distance, and addressing weather-related barriers and health related motivators.